Inactivation of SARS-CoV-2 in chlorinated swimming pool water. (15th October 2021) - Brown, Jonathan C; Moshe, Maya; Blackwell, Alex; Barclay, Wendy S
Highlights: SARS-CoV-2 is susceptible to inactivation by chlorinated swimming pool water. At least 3-log10 reduction in the SARS-CoV-2 infectious titre observed after 30 s. SARS-CoV-2 inactivation by free chlorine is less effective at higher pH. Abstract: SARS-CoV-2 transmission remains a global problem which exerts a significant direct cost to public health. Additionally, other aspects of physical and mental health can be affected by limited access to social and exercise venues as a result of lockdowns in the community or personal reluctance due to safety concerns. Swimming pools reopened in the UK on April 12th 2021, but the effect of swimming pool water on inactivation of SARS-CoV-2 has not yet been directly demonstrated. Here we demonstrate that chlorinated water which adheres to UK swimming pool guidelines is sufficient to reduce SARS-CoV-2 infectious titre by at least 3 orders of magnitude. Graphical abstract: Image, graphical abstract